Replication Data for Persistence of Individual and Social Preferences in Rural Settings - International Food Policy Research Institute; Escuela Superior Politécnica del Litoral (International Food Policy Research Institute, 2026)
This dataset contains the replication data files for the paper Persistence of Individual and Social Preferences in Rural Settings. The study examines the stability of individual and social preferences in rural settings, using the COVID-19 pandemic as a major global shock.